If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 13 + 2x + -1 = 45 + -2x + 33 Reorder the terms: 13 + -1 + 2x + 2x = 45 + -2x + 33 Combine like terms: 13 + -1 = 12 12 + 2x + 2x = 45 + -2x + 33 Combine like terms: 2x + 2x = 4x 12 + 4x = 45 + -2x + 33 Reorder the terms: 12 + 4x = 45 + 33 + -2x Combine like terms: 45 + 33 = 78 12 + 4x = 78 + -2x Solving 12 + 4x = 78 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 12 + 4x + 2x = 78 + -2x + 2x Combine like terms: 4x + 2x = 6x 12 + 6x = 78 + -2x + 2x Combine like terms: -2x + 2x = 0 12 + 6x = 78 + 0 12 + 6x = 78 Add '-12' to each side of the equation. 12 + -12 + 6x = 78 + -12 Combine like terms: 12 + -12 = 0 0 + 6x = 78 + -12 6x = 78 + -12 Combine like terms: 78 + -12 = 66 6x = 66 Divide each side by '6'. x = 11 Simplifying x = 11
| 75+.30x=105.60 | | 3x+4y=7+3 | | 14-7x-4x= | | 10.8=p*.5/2 | | .6x-14=-6.8+12.7x | | r/6=-8 | | -16t^2+112t+92=0 | | 3r+a-3+4s=7 | | 5(x+16)=15x+30 | | 1.5(x+8)=2.1+0.6x | | y-3=0.4(x-5) | | 2(x-7+x)=(x+9)+(x+2)+(x-7) | | (2c^2+c-3)(3c-1)=0 | | 3x+6=(-15) | | 5(x+7)=x-2 | | 7/4x=14/3 | | (-3X^2+5X+2)(4X^2-3X)=0 | | 3+3(2y-8)-3(4y+4)-10= | | 4w-26=38 | | 10x-4y=k | | 6a=14a | | -4x-36=34-6x | | 8(x+6)=8x+32 | | 3a+4b-3+4a=7 | | 8x+36=12x-20 | | 4x+40=16 | | 3x+4y=3-2 | | 6(x-12)+5(x-13)=6 | | X+.6x=265 | | V=(a+4)(a-5)(2a) | | P=80-20q | | X-11=32 |